The sensitive detection of methylene blue using silver nanodecahedra prepared through a photochemical route. Issue 64 (23rd October 2020) - Vu, Xuan Hoa; Dien, Nguyen Dac; Ha Pham, Thi Thu; Trang, Tran Thu; Ca, N. X.; Tho, P. T.; Vinh, Nguyen Dinh; Van Do, Phan
Abstract : In this work, we have carried out systematic studies on the critical role of polyvinyl pyrrolidone (PVP) and citrate in the well-known chemical reduction route to synthesize silver nanodecahedra (AgND). Abstract : In this work, we have carried out systematic studies on the critical role of polyvinyl pyrrolidone (PVP) and citrate in the well-known chemical reduction route to synthesize silver nanodecahedra (AgND). Silver nitrate (AgNO3 ) was used as silver source, which can be directly converted to metallic silver after being reduced by sodium borohydride (NaBH4 ) under blue light-emitting diode (LED) irradiation ( λ max = 465 nm), and polyvinyl pyrrolidone (PVP) as a capping agent to assist the growth of AgND. The obtained products were silver nanodecahedra of excellent uniformity and stability with high efficiency and yield. The results showed that PVP acted as a capping agent to stabilize the silver nanoparticles, prolonging the initiation time required for nanodecahedra nucleation, thus inducing anisotropic growth, allowing the size and morphology of the AgND to be controlled successfully. This improved understanding allows a consistent process for the synthesis of AgND with significantly enhanced reproducibility to be developed and the formation mechanism of these nanostructures to be elucidated. This is a simple, cost-effective and easily reproducible method for creating AgND. The typical absorption maxima in the UV-vis spectroscopy of Ag seeds was λ max ∼400 nm and that of AgND was λ max ∼480 nm. The size of the prepared AgND was in the range of 60–80 nm. SEM images confirmed the uniform and high density of AgND when the concentration of PVP was 0.5 mM. The XRD pattern showed that the final product of AgND was highly crystallized. In addition, the prepared AgND can be used to detect methylene blue (MB) in a sensitive manner with good reproducibility and stability using Surface-Enhanced Raman Scattering (SERS) phenomenon. Out of the obtained products, the AgND prepared with 50 min blue LED light irradiation (AgND-50) displayed the strongest SERS signal. Interestingly, MB in diluted solution can be detected with a concentration as low as 10 −7 M (the limit of detection, LOD) and the linear dependence between SERS intensity and the MB concentration occurred in the range from 10 −7 to 10 −6 M. The enhancement factor (EF) of the SERS effect was about 1.602 × 10 6 with a MB concentration of 10 −7 M using 532 nm laser excitation.